1996
DOI: 10.1093/jmedent/33.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Ixodes (Ixodes) scapularis (Acari: Ixodidae): Redescription of all Active Stages, Distribution, Hosts, Geographical Variation, and Medical and Veterinary Importance

Abstract: The blacklegged tick, Ixodes (Ixodes) scapularis Say, 1821, is redescribed, based on laboratory reared specimens originating in Bulloch County, Georgia. Information on distribution, host associations, morphological variation, and medical/veterinary importance is also presented. A great deal of recent work has focused on this species because it is the principal vector of the agent of Lyme disease (Borrelia burgdorferi Johnson, Schmidt, Hyde, Steigerwaldt & Brenner) in eastern North America. Its distribution app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
141
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(143 citation statements)
references
References 0 publications
2
141
0
Order By: Relevance
“…Areas that are suitable but not currently sustained are those that will experience the greatest increase in I. scapularis population density, because introductions should result in reproducing populations. The presence of these areas validates the idea that I. scapularis continues to expand its range (Dennis et al 1998;Keirans et al 1996). According to the model, notable increases in vector distribution are expected in Virginia, North Carolina, Georgia, Minnesota, Iowa, and Michigan.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Areas that are suitable but not currently sustained are those that will experience the greatest increase in I. scapularis population density, because introductions should result in reproducing populations. The presence of these areas validates the idea that I. scapularis continues to expand its range (Dennis et al 1998;Keirans et al 1996). According to the model, notable increases in vector distribution are expected in Virginia, North Carolina, Georgia, Minnesota, Iowa, and Michigan.…”
Section: Discussionsupporting
confidence: 65%
“…I. scapularis is the primary vector of Borrelia burgdorferi, the agent of Lyme disease, in North America (Dennis et al 1998;Keirans et al 1996). Lyme disease is currently the most prevalent vectorborne disease in the United States, with more than 100,000 cases reported by the U.S. Centers for Disease Control and Prevention since its discovery in 1982 (Orloski et al 2000).…”
mentioning
confidence: 99%
“…This trend is clearly shown by the spreading of suitable area north into Canada. Though I. scapularis has been collected from a variety of locations in Canada (Keirans, Hutcheson et al 1996;Scott, Fernando et al 2001), establishment has only been shown for a limited number of locations in southern Ontario (Lindsay, Artsob et al 1998;Barker and Lindsay 2000). Climate change may provide the conditions necessary to yield reproducing populations of I. scapularis either by the systematic advancement from south of the border by movement on mammal hosts or by adventitious introductions from attachment to bird hosts (Klich, Lankester et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The tick, Ixodes scapularis, the primary vector of Lyme disease in North America (Keirans, Hutcheson et al 1996;Dennis, Nekomoto et al 1998), is highly dependent on climate patterns (Stafford 1994;Lindsay, Barker et al 1995;Bertrand and Wilson 1996). The abiotic environment plays a vital role in the survival of I. scapularis with both water stress and temperature regulating off-host mortality (Needham and Teel 1991;Bertrand and Wilson 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Larval I. scapularis are not host-specific and have been found to feed on many vertebrate species (17). On the basis of previous studies (18,19), we anticipated that the impact of vaccination on reducing nymphal infection prevalence would correlate positively with the proportional role that mice play in infecting larvae.…”
mentioning
confidence: 99%